Fire and explosion hazards handbook of industrial chemicals - Davletshina, Tatyana (Noyes Publications, 1998)
This handbook provides ready information on the fire and chemical reactivity of commonly used chemicals. Its purpose is to provide basic information important to the safe handling of chemicals and to help provide guidance in responding to a hazardous materials incident, in particular, incidents involving reactive chemicals and materials posing fire and explosion hazards. This volume has been written for chemical handling specialists, first responders to hazardous materials incidents, and firefighters. The basic definition used for a hazard materials incident is any situation that may potentially lead to catastrophic fire or explosion, and or human exposure to a toxic chemical. This situation may result from a spill of a hazardous material, a leak from a storage vessel or shipping container, or the mixing of incompatible chemicals whereby a chemical reaction could occur resulting in the release of energy and generation of toxic and perhaps flammable by-products.